Variaciones geoquímicas y deformación en superficie del Volcán Copahue asociadas al ciclo eruptivo 2012-2016 - Agusto, Mariano Roberto (2017)
The 2012-2016 Copahue volcano eruptive cycle was characterized by precursory signals observed from surface deformation and geochemistry of volcanic fluids. These signals are associated with the magmatic input that triggers the explosive events that initiate the eruptive cycle. Subsequetn variations respond to the instability of the system controlled by the interaction between the magmatic and hydrothermal components throughout the 2012-2016 cycle.